Practices Of Productive Waqf Management, Development And Utilisation By Waqf Managers In Islamic Boarding Schools In Maros Regency - Samsidar Jamaluddin; Muammar Muh. Bakry; Muhammad Shuhufi; Abd. Rauf Muhammad Amin (Gudang Jurnal Multidisiplin Ilmu, 2025)
The study aims to explain the practices of productive waqf management, development, and utilisation by waqf managers in Islamic boarding schools in Maros Regency. This is a qualitative study. The research design is field research. The results of this study indicate that: The management of productive endowments at the Raudaturrasyidin DDI Cambalagi Islamic boarding school is categorised as unproductive with insignificant income growth due to irregular harvests throughout the year. The realisation of the utilisation of profits from productive endowment income at the Raudaturrasyidin DDI Cambalagi Islamic Boarding School. Meanwhile, the management of productive endowments at the Nurul Ikhwan Islamic Boarding School through the boarding school canteen is categorised as productive with a significant increase in income. Meanwhile, the management of productive endowments at the Nahdlatul 'Ulum Islamic Boarding School through the mini market Aminah demonstrates productive management of productive endowments on endowed assets, namely the Mini Market Aminah, which is categorised as moderately productive with significant income growth from May to December 2023 and May to December 2024. Each portion of the income from productive endowments at the three boarding schools has a designated allocation for utilisation. On the other hand, development aspects are not being implemented at the pond managed by the al-Irsyad Foundation.